KUALITAS NUTRIEN DAN KECERNAAN IN VITRO BEBERAPA PAKAN LOKAL TERNAK KAMBING DI LAHAN KERING KEPULAUAN - Hadisutanto, Bambang; Bachtaruddin Badewi,; Fransiska K. Banola,; Abner Tonu Lema, (Jurnal Peternakan Nusantara, 2022)
This study aims to determine the nutritional quality and digestibility value of dry matter and organic matter of local feed. The research was carried out at the Nutrition and Animal Feed Laboratory of the Kupang State Agricultural Polytechnic for 2 months. The variables observed were nutrient quality and dry matter and organic matter digestibility in vitro. The results of the analysis showed the average nutrient content of local feed ingredients, namely gamal leaf (BK 93.77%), putak flour (BO 90.33%), fish meal (PK 43.45%), fish meal (LK 4.61% ), rice bran (SK 29.84%), fish meal (KA 39.44%). The highest organic matter digestibility was in putak flour 66.47%, followed by fish meal 57.76%, gamal leaf 56.42%, corn husks 47.52%, and rice bran 40.78%. The conclusion of this study is that local feed ingredients for goats, namely rice bran, corn husks, fish meal, putak flour and gamal leaves can be recommended as animal feed.